Dynamic Load on a Pipe Caused by Acetylene Detonations – Experiments and Theoretical Approaches - Axel Sperber; Hans-Peter Schildberg; Steven Schlehlein (Shock and Vibration)
The load acting on the wall of a pipe by a detonation, which is travelling through, is not yet well characterized. The main reasons are the limited amount of sufficiently accurate pressure time history data and the requirement of considering the dynamics of the system. Laser vibrometry measurements were performed to determine the dynamic response of the pipe wall on a detonation. Different modelling approaches were used to quantify, theoretically, the radial displacements of the pipe wall. There is good agreement between measured and predicted values of vibration frequencies and the propagation velocities of transverse waves. Discrepancies mainly due to wave propagation effects were found in the amplitudes of the radial velocities. They might be overcome by the use of a dynamic load factor or improved modelling methods.